Анализ эффективных форм предпринимательской деятельности в России (Путеводитель предпринимателя)
In article the analysis of effective forms of enterprise activity in Russia is carried out: individual business, partnership and corporation. It is shown that development of the Russian business and a choice of forms of enterprise activity should be carried out taking into account real Russian economic, legal and social-cultural conditions.